Defecation into clothing without forewarning and mean radiation dose to bowel and anal-sphincter among gynecological cancer survivors. (1st November 2016) - Lind, Helena; Alevronta, Eleftheria; Steineck, Gunnar; Waldenström, Ann-Charlotte; Nyberg, Tommy; Olsson, Caroline; Wilderäng, Ulrica; Dunberger, Gail; al-Abany, Massoud; Åvall-Lundqvist, Elisabeth
Abstract: Background: To analyze the relationship between mean radiation dose to the bowels and the anal-sphincter and occurrence of 'defecation into clothing without forewarning', a specific and serious fecal incontinence symptom after gynecological radiotherapy. Additional potential risk factors associated with the symptom are explored. Material and methods: Data were collected for 519 eligible gynecological cancer survivors, treated with pelvic radiotherapy, with a median follow-up of 5.8 years, using a study-specific questionnaire and medical records. Correlations between defecation into clothing without forewarning and mean dose to organs at risk; the anal-sphincter region, the rectum, the sigmoid and the small intestines were investigated, also taking other risk factors into account. Results: Twelve percent reported having had the symptom at least once in the preceding six months. Mean doses >50 Gy to the anal-sphincter region, the rectum, the sigmoid and the small intestines were related to the occurrence of the symptom. Significantly associated risk factors were deliveries with high birth weight, heart failure and lactose and/or gluten intolerance. After adjusting for these factors, mean doses >50 Gy to the anal-sphincter region, the sigmoid and the small intestines remained related to the occurrence of the symptom. Conclusion: Mean doses to the bowels and anal-sphincter region are related to the risk of defecation into clothing without forewarning in long-term gynecological cancer survivors treated with pelvic radiotherapy. Further radiobiological modeling may distinguish which organ(s) contribute most to development of the symptom.